Evaluation of the commercial AD fosfomycin test for susceptibility testing of multidrug-resistant Enterobacterales and Pseudomonas aeruginosa. (May 2021) - Parisio, Eva Maria; Camarlinghi, Giulio; Coppi, Marco; Niccolai, Claudia; Antonelli, Alberto; Nardone, Maria; Vettori, Chiara; Giani, Tommaso; Mattei, Romano; Rossolini, Gian Maria
Abstract: Objectives: To compare fosfomycin susceptibility testing with the commercial agar dilution (AD) test, AD Fosfomycin (Liofilchem, Roseto degli Abruzzi, Italy) and the reference AD method, using a collection of multidrug-resistant (MDR) Enterobacterales and Pseudomonas aeruginosa clinical isolates. Methods: The collection included 119 carbapenemase-producing Enterobacterales, 53 Enterobacterales producing acquired AmpC-type and/or extended-spectrum β-lactamases and 38 carbapenemase-producing P. aeruginosa, including representatives of different high-risk clones. AD Fosfomycin and AD reference method (ISO 20776-1:2019) were performed starting from the same microbial suspension. Results were interpreted according to EUCAST clinical breakpoints (10.0). Essential agreement (EA), category agreement (CA) and error rates were calculated as described by the International Organization for Standardization. Results: Of 172 Enterobacterales, 143 (83.1%, including 92.9% (52 of 56) of the NDM-producers and 84.2% (48 of 57) of the KPC-producers) were susceptible to fosfomycin using reference AD. A CA of 91.9% (158 of 172; 95% CI 87.1%–95.3%) and an EA of 92.5% (136 of 147; 95% CI 87.4%–96.0%), respectively, were calculated for the commercial AD Fosfomycin test, with 9.8% (14 of 143) of major errors and no very major errors (0 of 29). Overall, 86.8% (33 of 38) of P. aeruginosa showed a fosfomycin MIC ≤128 mg/L using reference AD. An EA of 84.8% (95% CI 66.3%–92.0%) was calculated for the commercial AD Fosfomycin test, with a CA of 100% (95% CI 93.6%–100%) when considering a tentative breakpoint at 128 mg/L. Conclusions: AD Fosfomycin showed an overall good concordance compared with reference AD.